The impact of empowerment theory-based health education on Alzheimer’s disease informal caregivers: a randomized controlled trial - Liu, Xiaofeng; Wang, Shurui; Wei, Lirong; Liu, Yun; Bian, Jiping; Wang, Shen; Du, Xian (Frontiers in Public Health, 2024)
Background There is a lack of evidence regarding the effectiveness of empowerment healthy education for caregivers of Alzheimer’s patients. Objective To explore the effectiveness of the intervention of health education guided by empowerment theory on dementia knowledge, caregiving readiness, positive caregiving emotions, anxiety, and depression in informal Alzheimer’s disease caregivers. Design A single-blinded, randomized controlled trial. Setting A teaching hospital in Tianjin, China. Participants Eighty caregivers of Alzheimer’s disease patients. Methods Participants were recruited from the hospital and randomly assigned to either experimental or control group. The experimental group underwent a 12-weeks, one-to-one intervention of six session lasting 45–60 min each. The control group received conventional health education. Outcome measures included dementia knowledge, caregiver readiness (primary outcomes), positive caregiving emotions, anxiety, and depression (secondary outcomes). Results After 12 weeks, the intervention group exhibited significantly higher levels of dementia knowledge, caregiver readiness, and positive caregiving emotions compared with the control group. Furthermore, levels of hospitalization-related anxiety and depression were lower in the intervention group. All study results of this study showed statistically significant differences (p < 0.05). Discussion Empowerment theory-based health education appears to be an effective intervention for improving caregiver and readiness to care for caregivers of Alzheimer’s disease individuals. The intervention may help reduce caregivers’ anxiety and depression levels.